982 ARE POST FALL CT HEAD SCANS DONE ACCORDING TO TRUST GUIDELINES. (14th June 2022) - Rahman, M M; Ezeigwe, O
Abstract: Introduction: Falls are a major public health concern, which poses a high risk of injury and even death. Due to fears regarding increased morbidity and mortality post fall, we have noticed that there is a tendency for junior doctors to request computerized tomography (CT) head scans beyond clinical reasoning and indications that are not found in the trusts post falls protocol. In addition, we discovered significant delays in completion of inpatient CT head scans resulting in delayed management. We therefore embarked on an audit with the aim of improving post falls assessment. We assessed compliance with trust post fall protocol regarding suspected head injury and requesting of urgent CT head scans, if urgent CT had scan are done within 1 hour and carrying out neurological observations post fall. The initial audit outcomes demonstrated poor compliance with the audited standards. As a result we introduced a new comprehensive post falls assessment proforma. Results: We re-audited after the introduction of the new falls proforma, assessing inpatient falls from 20th January to 27th February 2021 at the William Harvey Hospital. 69% of falls cases have CT head scans requested as per trust policy, an improvement of 77% from the initial audit. 50% of patients who met the criteria for urgent CT head scans had it done within one hour of the request being made, an improvement of 150%. 84% of patient's had neurological observations recorded as part of post fall assessment, an improvement of 12% from the initial audit. Conclusion: The improvements seen in the audited standards are indicative that the new post falls proforma improves compliance with the trusts post falls protocol. We recommend that the new post falls proforma be a part of the trusts post fall protocol and for it to be included in the trust induction to new doctors.